An analysis of the Genetics Polymorphisms of the Serotonin (5-H T) Receptor (Article Review) - AL-Fatlawy, Hawraa Natiq Kabroot; Hamza Al-Kraity, Asst.Prof.Dr. Wijdan Rajh; Mohammed, Zainab Sajid (Medical Science Journal for Advance Research, 2023)
Serotonin, also known as 5-hydroxytryptamine or 5-HT, is a crucial neurotransmitter in the human body, responsible for regulating various biological functions. It is often referred to as the "happy chemical" due to its role in promoting well-being and happiness. The body synthesizes 5-HT from the essential amino acid L-tryptophan, which is obtained from dietary protein. Serotonin receptors are divided into seven families, numbered 5-HT1 through 5-HT7. Certain families, such as 5-HT1A, 5-HT1B, 5-HT1C, 5-HT1D, 5-HT1E, and 5-HT1F, have multiple members. When taking antidepressants, there is a risk of developing the serotonin syndrome, which is a medication-induced condition resulting from serotonergic hyperactivity. As the number of patients with medically-treated major depressive disorder increases, so does the likelihood of experiencing serotonin syndrome. The serotonin transporter (also known as SLC6A4) and monoamine oxidase A (MAOA) are two molecules responsible for regulating serotonin levels in the brain. Genetic polymorphisms in the promoter regions of the genes encoding these proteins have been shown to affect their transcriptional activity in vitro. HTR2A has been identified as a gene that may increase susceptibility to rheumatoid arthritis (RA). In this study, we conducted an analysis to investigate the association between DNA methylation of HTR2A and RA using samples of peripheral blood.